Pelatihan Media Pembelajaran Aplikasi Quizizz Siswa Sekolah Dasar pada Masa Pandemi Covid-19 - Sukiyanto Sukiyanto; Tsalitsatul Maulidah; Dewi Anggreini; Denik Agustito; Dwi Nova Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
This PkM training activity aims to provide training on how to utilize technology, namely the use of free online gamification features to assist the teaching and learning process outside the classroom using the Quizizz application. The implementation method used is socialization, training implementation and evaluation. The subject of this training was attended by 15 sixth grade students. The results show that the application can increase student learning concentration and can increase enthusiasm in learning in the midst of the Covid-19 pandemic so that online learning feels more fun and students can learn while playing through this Quizizz application. This training also has a significant impact on the ability of teachers to develop learning evaluation instruments using the Quizizz application.